Social Media Activity dan Customer Experience dalam Membentuk Relationship Quality - Barbara Suha; Kurnia (Jayapangus Press, 2021)
Social media activities and positive user experiences are very important for Public Relations (PR) strategy in three aspects, namely as a media for presentation, communication, and improving PR performance, where social media activities that can be in line with users' positive experiences will be able to function to show organizational identity, create communication, direct decision making and improve the organization's mutual relationship strategy with its publics. This study aims to understand the relationship between social media activity and customer experience in establishing relationship quality which is implemented in specific insurance companies through a study approach at PT Asuransi Jiwa Astra, which was later known as Astra Life. This research method uses a quantitative approach using the positivism paradigm. The research population is Astra Life's active customers and 100 respondents are assigned as a representative sample. Data were collected through an online survey and analyzed using the Partial Least Square (PLS) method. The results of the study indicate that Social Media Activity and Customer Experience have a positive effect in shaping Relationship Quality. The results of this study also show that Social Media Activity and Customer Experience are very strong in explaining the success of Astra Life's PR Relationship Quality strategy approach with customers so that further research can also identify Social Media Activity and Customer Experience approaches in building Relationship Quality in similar service industries in order to obtain findings. the benefits of research in the field of communication Public Relations are more diverse.